Fibroblast growth factor receptor expression in hemangioblastomas: A novel therapeutic target. - Maya Puttonen; Olli Tynninen; Sami Salmikangas; Tiina Vesterinen; Harri Sihto; Tom Böhling (PLoS ONE)
Hemangioblastoma is a highly vascularized, benign tumor in the central nervous system, frequently associated with von Hippel-Lindau (VHL) disease. Hemangioblastoma may cause tumor-associated hemorrhage or exert pressure on nearby structures, leading to life-threatening complications. Although surgical resection is the primary treatment, complete removal is not always feasible. Accordingly, there is a need to explore targeted or anti-angiogenic therapies. The fibroblast growth factor receptor (FGFR) family has roles in tumorigenesis and angiogenesis, making it a potential target in personalized therapy. The distribution and significance of FGFRs in hemangioblastoma have yet to be investigated. We examined 139 formalin-fixed, paraffin-embedded hemangioblastoma samples from 111 patients, including sporadic cases and those associated with VHL disease. Immunohistochemistry revealed positive staining for FGFR2 (95%) and FGFR4 (61%), while FGFR1 (0%) and FGFR3 (12%) were mainly negative. FGFR2 expression was significantly increased in VHL-mutated tumors (75%, p = 0.034) and in male patients (68%, p = 0.020). Tumors located in the cerebrum (n = 6, 5%) had a higher likelihood of positive FGFR4 staining (100%, p = 0.009). Additionally, a larger tumor diameter was associated with a higher likelihood of FGFR4 expression (median 12.0 mm vs 17.5 mm, p = 0.018), suggesting its contribution in tumor growth. Our study revealed the expression of FGFR2 and FGFR4 in a significant number of hemangioblastomas. This finding demonstrates the potential of FGFRs as promising therapeutic targets for patients with hemangioblastoma.